2016
DOI: 10.1088/1674-1137/40/11/117003
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission characteristics of graphene films with copper substrate

Abstract: Secondary electron emission characteristics of graphene films with copper substrate * Jie Wang( ) Yong Wang( ) 1) Yanhui Xu( ) Yuxin Zhang( ) Bo Zhang( ) 2) Wei Wei( )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The results obtained are shown in Fig. 2, which also includes experimental data reported by Wang 27 and Xie. 28 The following aspects are evident from the plots: (a) Predictions of the SEY values are generally in good agreement with the measurements for a graphene coated copper substrate.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 54%
See 2 more Smart Citations
“…The results obtained are shown in Fig. 2, which also includes experimental data reported by Wang 27 and Xie. 28 The following aspects are evident from the plots: (a) Predictions of the SEY values are generally in good agreement with the measurements for a graphene coated copper substrate.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 54%
“…24,25 More recent studies of energy-dependent SEY for graphene coated copper systems have been reported, and they all point to the benefits of this approach. [26][27][28] However, numerical studies of SEY on graphene coated copper have not been performed, nor have careful comparisons with experimental data been made. The present study represents an effort in this direction.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
See 1 more Smart Citation
“…The electron cloud is a key problem in particle accelerators, which can cause the degradation of beam quality and limit the performance of particle accelerators with high energy, high intensity, high luminosity and long beam lifetime [1][2][3][4][5][6][7][8]. The methods of mitigating electron cloud effect have been studied by many researchers from several organizations, such as CERN [9,10], STFC [11,12], NSRL [13], KEK [7,14], INFN [15], etc. C. Yin Vallgren et al found that a complete suppression of e-cloud can be achieved by amorphous carbon coating of liners [9].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium nitride, chromium nitride and carbon nitride are typical candidates [20]. The effect of thickness, elemental content and geometric morphology of the novel coatings on reducing SEY have been investigated [21,22]. Based on the measured SEY, numerical simulation is employed to calculate multipactor threshold and to ensure the effectiveness and feasibility of proposed treatment approaches for microwave power components [23,24].…”
mentioning
confidence: 99%